Analisis Pengaruh Pengambilan Keputusan Pembelian Mesin Packing dengan Menggunakan Metode Capital Budgeting Pada CV. Basalamah - Utomo, Eko Budi; Putra, M Hengki Riawan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study discusses the feasibility of investing in a packing machine at CV. Basalamah using the discounted payback period and profitability index methods, as part of Capital Budgeting analysis. This method helps the company assess investment decisions financially, as it is easy to understand and offers various calculation techniques. CV. Basalamah, which produces macaroni snacks, is facing high demand and plans to increase production capacity. Since the investment in a packing machine requires a large amount of capital, a feasibility analysis is necessary to ensure accurate decision-making. The main focus of this study is on financial aspects, while also considering other interrelated factors.